English as a medium of instruction in South Asia : issues in equity and social justice - Giri, Ram Ashish; Padwad, Amol; Naushaad Kabir, Mian Md (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2024)
"This book examines the 'English mania phenomenon' and the complex circumstances of adopting English Medium Instruction (EMI) by South Asian education systems and the effect of an uneven distribution of resources on the already under-resourced countries in the region. Chapters explore linguistic, social, and economic injustices by using an analytic-critical approach to examinations of the place, role, provisions, and practices of EMI in specific English language teaching (ELT) contexts. The book consequently advocates for the wholescale reform of a system, which, the authors argue, is unjust. Ultimately, the book explores socio-cultural, poststructuralist, and English linguistic imperialism theories to contribute a South Asian perspective on the controversy surrounding EMI and examine its role within a wider global discourse on equity and social justice. Critically examining the spread of English in South Asia, this book will be of relevance to researchers, scholars, and postgraduate students in applied linguistics, language education, TESOL, and sociolinguistics"--
EMI in South Asia : the ideological underpinnings and practical contradictions / Ram Ashish Giri, Amol Padwad, Mian Md. Naushaad Kabir -- EMI in the multilingual ecology of South Asia : historical development, shifting paradigms, and transformative practices / Shaila Sultana -- Medium of education and inequality in university admission tests : exploring the case of a flagship university in Bangladesh / Mohammod Moninoor Roshid, Golam Kader Zilany, Noshin Afroz -- Social construction of EMI in India : situating EMI within the multilingual education paradigm / Padmini Boruah, A.K. Mohanty -- EMI, ELT and social justice : case of Pakistan / Fauzia Shamim -- English, EMI and social justice : the South Asian (hi)story / Amol Padwad -- English medium education in Sri Lanka : from colonial to postcolonial period / S.A. Kularathne, T Karunakaran-- Bhutanese education system : a historical journey / Pema Dendup -- Trajectory of English medium education (EMI) in a post-war community : a historical perspective from Jaffna, Sri Lanka / Karuna Sivaji, Maheswara Kurukkal Saravanapava Iyer -- English as medium of instruction and social justice in higher education in Bangladesh and Nepal : a capability perspective / Prithvi N. Shrestha, Sayeedur Rahman, Bharat Babu Shrestha -- Effectiveness of English medium instruction (EMI) at the undergraduate level at the University of Dhaka / Tazin Aziz Chaudhury & Rumana Rafique -- Issues of English language and social justice : towards bridging the gap between language education policy and practices in India / A.L. Khanna, Ruchi Kaushik -- Building or bridging the gap : issues and perspectives on linguistic ecology, social justice and EMI in the context of Pakistan / Urooj Yahya, Rahila Huma Anwar, Sajida Zaki -- EMI in Pakistan : a capability-based evaluation / Tayyaba Tamim -- The long fingers of English" : the impact of EMI policies and ideologies on teacher education courses in the students' mother tongue in the Maldives / Naashia Mohamed -- Policy negotiations, equity, and social justice in EMI classrooms : a study of teachers' perspectives / Santosh Mahapatra, Anik Nandi -- Multi-layered framework of promoting social justices in ELT classrooms : a case of Nepal / Kamal Raj Devkota -- Afterword / Mahmud Hasan Khan.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: English-medium instruction -- South Asia; English language -- Study and teaching -- South Asia; Language and education -- South Asia; Social justice and education -- South Asia